PUBLIC ADMINISTRATION IN CONDITIONS OF WAR: STRATEGIES FOR ENSURING FOOD SECURITY - Bondarchuk, N. V.; Dziurakh, Yu. M. (The actual problems of regional economy development, 2024)
The article is aimed at researching the issues of ensuring food security of Ukraine in modern conditions. The purpose of the article is to consider the impact of Russia's military aggression against Ukraine on the country's food security and to develop management strategies and measures aimed at ensuring the stability of food security in the conditions of war. The article uses methods of synthesis and analysis to determine strategies for ensuring the food strategy. The work states that the development and implementation of effective food security management strategies is critically important for ensuring the life safety and health of the local population. It is suggested that food security should be understood as the state of the national economy system, which ensures the food sovereignty of the state, that is, the ability to provide the urgent needs of the population for quality products, economic and physical availability of food products, as well as compliance of products with internal and external quality standards. propose a number of countermeasures against threats to food security of Ukraine: analysis, assessment of threats to food security and existing countermeasures in Ukraine and in the regions in particular; formation of a food safety and vulnerability monitoring system for forecasting possible emergency events in order to improve the development of contingency plans; cooperation with international organizations on exchange of experience in the field of food safety; planning and formation of reserves of essential food products in case of emergencies and others. It is proposed to implement the "green economy" strategy. "Green economy" is aimed at reducing the negative impact on the environment, efficient use of resources and promoting the preservation of natural ecosystems. The implementation of this strategy will improve the condition of the soil cover, which will lead to the development of the agro-industrial complex and increase the level of food security of the state and regions in particular. In addition, it is stated that the food security of the country can be ensured only within the framework of an integrated approach, while its basic components must be fixed at the legislative level. Our country has to build an effective food policy taking into account all the accumulated experience.